Designing Social Studies Brain-based Lesson Plan using Activation, Connection, and Transfer (ACT) Model - John Albert R Dela Rosa (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study develops a model for designing brain-based lesson plans in Secondary Social Studies. The developed model may serve as a reference for developing brain-based lesson plans grounded in an understanding of how the brain learns and works effectively. Methodology: This study employed a developmental research design. The research data were gathered through the validation of lesson plans, observation of lesson try-outs, focus group discussions, semi-structured interviews, and other techniques such as student behavioral measures, emoticons, ratings, and metaphors. Descriptive statistics were used to analyze the quantitative data, while a thematic analysis was utilized for analyzing qualitative data. Main Findings: The results indicated that when applying the ACT Model in instruction, Social Studies teachers should begin by activating students’ brains through engaging and enjoyable learning activities that present essential concepts at the start of the lesson. This should be followed by connecting the lesson to the students’ life experiences. Lastly, to demonstrate relevance, the Social Studies lesson should conclude by transferring students’ learning into their lives more realistically, allowing them to practice and internalize the content. Novelty/Originality of this study: This study advances academic discourse on applying brain science to social studies education. It highlights the importance of integrating neuroscience with social studies education to design scientifically sound teaching methods. Additionally, it contributes to the field of research by outlining a process for developing a learning model aimed at enhancing social studies education.